2015
DOI: 10.1007/s00404-015-3767-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Vaginal progesterone for prevention of preterm labor in asymptomatic twin pregnancies with sonographic short cervix: a randomized clinical trial of efficacy and safety

Abstract: Vaginal progesterone administration in asymptomatic twin pregnancies with sonographic short cervix (20-25 mm) at 20-24 weeks of gestation is effective and safe treatment for reducing the incidence of preterm labor with subsequent reduction in the neonatal morbidities and mortality associated with preterm birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 27 publications
0
93
0
6
Order By: Relevance
“…16 Conversely, and at variance with present findings, other clinical trials concluded that vaginal progesterone, administration in asymptomatic twin pregnancies with a sonographic short cervix (20-25 mm) at 20-24 weeks of gestation was found effective and safe treatment for reducing the incidence of preterm labor. 17,18 In view of arguable issues concerning the efficacy of the use of progesterone or cerclage alone in preventing preterm birth in twin gestations, present study by far, may be one of only few if any, in the accessible literature which evaluated a dual approach of both progesterone and cervical cerclage in prevention of preterm labour in twin gestation. In current study, combined progesterone as well as cerclage was found efficacious in reducing preterm labour prior to 34 weeks and 34-37 weeks of gestation with a statistically significant difference when compared to either progesterone or cerclage groups while there was no significant difference between the two latter groups.…”
Section: Discussionmentioning
confidence: 99%
“…16 Conversely, and at variance with present findings, other clinical trials concluded that vaginal progesterone, administration in asymptomatic twin pregnancies with a sonographic short cervix (20-25 mm) at 20-24 weeks of gestation was found effective and safe treatment for reducing the incidence of preterm labor. 17,18 In view of arguable issues concerning the efficacy of the use of progesterone or cerclage alone in preventing preterm birth in twin gestations, present study by far, may be one of only few if any, in the accessible literature which evaluated a dual approach of both progesterone and cervical cerclage in prevention of preterm labour in twin gestation. In current study, combined progesterone as well as cerclage was found efficacious in reducing preterm labour prior to 34 weeks and 34-37 weeks of gestation with a statistically significant difference when compared to either progesterone or cerclage groups while there was no significant difference between the two latter groups.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank Dr. Aeli Ryu, Dr. Tae-Hee Kim and Dr. Hae-Hyeog Lee for their interest in our study [1] and their valuable comments [2].…”
Section: Dear Editormentioning
confidence: 97%
“…Estos estudios abren la puerta al uso de cerclaje profiláctico en pacientes con embarazo gemelar bien seleccionadas, haciendo manifiesta la necesidad de realizar estudios clínicos las 34 semanas del 33% RR 0,67 [IC 95% 0,49-0,90], así como también de parto prematuro antes de las 32 semanas EG, RN menores de 1500 y 2500 grs, síndrome de distress respiratorio, mortalidad neonatal precoz y necesidad de ventilación mecánica en los recién nacidos del grupo expuesto a progesterona (22). Lo relevante de este trabajo es que es el primer ECR que ha demostrado que progesterona vaginal en dosis de 400 mg diarios, podría reducir el parto prematuro en embarazos gemelares con LC ≤ 25 mm.…”
Section: Progesteronaunclassified
“…En 3 de estos se utilizó 17-OH Caproato de progesterona intramuscular y en los otros 9, progesterona micronizada vaginal en dosis de 200 a 400 mg diarios. Solo en uno de estos estudio se consideró la longitud cervical como criterio de inclusión (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Es así, como en el grupo general de embarazo múltiple, es decir con cervicometria normal o desconocida, parece claro que el uso de progesterona, ya sea natural o sintética, no tiene mayor utilidad.…”
unclassified